2005
DOI: 10.1063/1.1867565
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mg doping in high-Al content p-type AlxGa1−xN (0.3<x<0.5)

Abstract: A study of Mg doping of AlxGa1−xN up to x∼50% using microstructural and electrical probes is reported. The viability of effective p-type doping is defined by a minimum concentration of Mg required to offset the background impurities and, more importantly, a maximum limit above which inversion domains and structural defects start to nucleate, accompanied by a rapid degradation of electrical transport. Resistivity of 10 Ω cm and free hole concentrations above 1017cm−3 are achieved for AlxGa1−xN up to x∼50% withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 10 publications
1
48
0
1
Order By: Relevance
“…Most of the investigations focus on p-type AlGaN epilayers with an Al fraction that is less than 20%. Recently, Jeon et al [13] reported that the viability of low resistivity p-AlGaN doping is constrained by two competing mechanisms, namely, a minimum dosage of Mg acceptors required to overcome the background defects and an incorporation ceiling above which structural defects occur.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the investigations focus on p-type AlGaN epilayers with an Al fraction that is less than 20%. Recently, Jeon et al [13] reported that the viability of low resistivity p-AlGaN doping is constrained by two competing mechanisms, namely, a minimum dosage of Mg acceptors required to overcome the background defects and an incorporation ceiling above which structural defects occur.…”
Section: Introductionmentioning
confidence: 99%
“…At Al contents of x~0.45 a low resistivity of 8 Ω cm was obtained [69] at room temperature whereas at higher Al-content x~0.7 the resistivity increased to 100 000 Ω cm [112]. Recently a low resistivity of 47 Ω cm was reported for Al 0.7 Ga 0.3 N [114] indicating that there is a very narrow growth window for p-type doping at this Al contents.…”
Section: Mg Doping Of Alganmentioning
confidence: 98%
“…High Al-content p-type conductive Al x Ga 1-x N and AlN using Mg have been reported [10,108,69,[112][113][114]. At Al contents of x~0.45 a low resistivity of 8 Ω cm was obtained [69] at room temperature whereas at higher Al-content x~0.7 the resistivity increased to 100 000 Ω cm [112].…”
Section: Mg Doping Of Alganmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Jeon et al [13] reported p-type resistivity as low as 10 Ω cm in AlGaN epitaxial layers with an Al content of 0.3. The electrical characteristics of group III nitride epitaxial films are sensitive to the MOCVD growth conditions.…”
Section: Introductionmentioning
confidence: 99%